2018
DOI: 10.1186/s12935-018-0670-4
|View full text |Cite
|
Sign up to set email alerts
|

SKA3 promotes cell proliferation and migration in cervical cancer by activating the PI3K/Akt signaling pathway

Abstract: BackgroundCervical cancer (CC) is one of the most common cancers among females worldwide. Spindle and kinetochore-associated complex subunit 3 (SKA3), located on chromosome 13q, was identified as a novel gene involved in promoting malignant transformation in cancers. However, the function and underlying mechanisms of SKA3 in CC remain unknown. Using the Oncomine database, we found that expression of SKA3 mRNA is higher in CC tissues than in normal tissues and is linked with poor prognosis.MethodsIn our study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 49 publications
2
67
0
Order By: Relevance
“…Co-Ips indicated an interaction between SKA3 and EGFR, which influenced EGFR phosphorylation and activation. Similar to the present study, recent findings indicated that SKA3 promotes cell proliferation and migration in cervical cancer tissue through its ability to activate PI3K/Akt signaling [11]. However, we found that SKA3 interacts with EGFR to enhance PI3K-AKT activity, which was a novel finding.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Co-Ips indicated an interaction between SKA3 and EGFR, which influenced EGFR phosphorylation and activation. Similar to the present study, recent findings indicated that SKA3 promotes cell proliferation and migration in cervical cancer tissue through its ability to activate PI3K/Akt signaling [11]. However, we found that SKA3 interacts with EGFR to enhance PI3K-AKT activity, which was a novel finding.…”
Section: Discussionsupporting
confidence: 86%
“…SKA3 mutations are common in breast cancer, and were regulated cell growth [10]. Studies have shown that SKA3 mediates the metastatic profile and outcome of several cancers [11,12]. Using the GEPIA database to analyze LUAD tissue, SKA3 mRNA expression was elevated and correlated to poor survival outcomes in LUAD patients.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of gene enrichment analysis (GSEA), SKA3 was enriched in the cell cycle and P53 signaling pathways and these results were verified (Hou et al, 2019). Moreover, it has been reported that SKA3 can facilitate PI3K/AKT signaling pathway to promote cell cycle and progression in cervical cancer (Hu et al, 2018).…”
Section: Discussionmentioning
confidence: 67%
“…After the cells had attached, the medium in all wells was replaced with fresh culture medium for the controls or medium containing the respective compound concentrations. Four replicates of each concentration were tested to investigate the effect of berberine (3, 10, 30, 100, and 300 µmol/L) and matrine (1,3,10,30, and 100 mmol/L) against HeLa and SiHa cells. After incubating for 24 h, 20 µL of 5 mg/mL 3-(4,5dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) solution was added to each well, followed by incubation for 4 h in the incubator, after which the supernatant in each well was carefully discarded (24)(25).…”
Section: Cell Culture Assays 3-(45-dimethylthiazol-2-yl)-25-diphenymentioning
confidence: 99%